an=17+(n-1)(-4)

Simple and best practice solution for an=17+(n-1)(-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for an=17+(n-1)(-4) equation:


Simplifying
an = 17 + (n + -1)(-4)

Reorder the terms:
an = 17 + (-1 + n)(-4)

Reorder the terms for easier multiplication:
an = 17 + -4(-1 + n)
an = 17 + (-1 * -4 + n * -4)
an = 17 + (4 + -4n)

Combine like terms: 17 + 4 = 21
an = 21 + -4n

Solving
an = 21 + -4n

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Divide each side by 'n'.
a = 21n-1 + -4

Simplifying
a = 21n-1 + -4

Reorder the terms:
a = -4 + 21n-1

See similar equations:

| 3b^2=24 | | b(7b-4)=0 | | -6p-10=7(-6p-10)-10(9-3p) | | 144x^2= | | x=150-50 | | 9=7x+2x | | 5y=11y-24 | | 5x+2(y+8)=5 | | 3y+27x=-21 | | 2(x-4)(x-4)-7=13 | | 2n+11=0 | | 9=5x+4x | | 24x^3-8x^2+9x-3= | | y^2+2.56x^2=2.56 | | 2(x-4)2-7=13 | | 5x^3+25x^2-80x-400=0 | | -2.13=-0.71C | | f(6)=6 | | 3e+5=-e+1 | | 5=2c+1+5 | | x^2+2.56y^2=2.56 | | 165=4x-x^2 | | 5x+10+x^2+2x=40 | | 2x+5+2x=25 | | ((4x^4)-(8x^2)+(3))=0 | | 1/3(2x-0.5)=3/4(8/3x-5) | | 0=x^3-43x+42 | | 5x-4=15x+94 | | (4x^4-8x^2+3)=0 | | 2v+x=0 | | 2003-03-02-00-00_files/i0170000.jpg | | =0x^3-43x+42 |

Equations solver categories